Body image among three denominations of Jewish women in Israel. Issue 2 (3rd April 2017) - Handelzalts, Jonathan E.; Geller, Shulamit; Levy, Sigal; Vered, Tal; Fisher, Shimrit
ABSTRACT: Religious identity has been shown to be related to women's healthy body image, though research is still scarce, with most of it having been carried out in the context of the Christian religion. We used measures of positive body image (Body Appreciation Scale) and negative body image (Body Image Concern Inventory) as well as body care attitude (Body Care Subscale) to study 230 women belonging to three Jewish denominations in Israel in mid 2013. Compared to modern-Orthodox and secular Jewish women, ultra-Orthodox Jewish women were found to possess a more positive and less negative body image; they also exhibited more positive attitudes regarding body care. Regarding body satisfaction, modern-Orthodox women were shown to be significantly more satisfied than were the secular women. This reflects a continuum, ranging between secular, modern-Orthodox, and ultra-Orthodox women regarding body image in all its aspects. The possible protective power of religion regarding body image is discussed in light of possible underlining mechanisms.